OPTIMIZING RESEARCH PRODUCTIVITY: GRADUATE STUDENTS’ VIEW ON USING POP AND VOSVIEWER TOOLS - Rosmayanti, Vivit; Wahid, Areski; Ram, St. Wijdana (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
The increasing demand for high-quality academic publications has prompted the exploration of innovative tools to streamline the research process. We conducted a study to explore how graduate students perceive using tools like Publish or Perish (PoP) and VOSviewer to improve their research productivity. The research uses a mixed-method approach including surveys and interviews of graduate students in the Universitas Negeri Makassar postgraduate program. The results show that PoP allows effective literature searches and citation analysis, and VOSviewer enables a wide coverage visual exploration of bibliometric data, including research mapping and trend analyses. However, issues concerning technical know-how and tool access were highlighted. This study highlights the promising potential of incorporating PoP and VOSviewer into the existing academic writing curricula to help graduate students develop impactful work. The paper also discusses recommendations for better tool utilization and overcoming known challenges.